Analisis Unsur Intrinsik Dan Ekstrinsik Kumpulan Dongeng Daerah Jambi Untuk Materi Pembelajaran Bahasa Indonesia - Sijabat, desi natalia Cristina; Rasdawita, Rasdawita; Setyonugroho, Agus (Jurnal Ilmiah Dikdaya, 2024)
: This research is included in the type of qualitative research. And belongs to the descriptive type. Thistype of descriptive research is used to describe the analysis of the intrinsic and extrinsic elements of Jambiregional fairy tales for Indonesian language learning materials. In this case, the researcher will look at whatintrinsic and extrinsic elements are contained in Jambi regional fairy tales and find out what moral values arein Jambi regional fairy tales and find out what fairy tales are related to the CP of the seventh gradeIndependent Middle School curriculum. The results of the research are intrinsic and extrinsic elements as wellas teaching materials in Jambi Regional fairy tales which are contained in 5 books, namely a book with the titleLegend of Bukit Perak, a book with the title Legend of the Chinese Mirror Princess, a book with the title TheOrigin of the King of Jambi, a book with the title Lubuk Bumbun and the book with the title Kerinci RegionalFolklore about Putri Tangguk, for intrinsic elements it includes theme, characters, plot, setting, language styleand point of view, while for extrinsic elements it only includes moral values and social values, for valuesreligion was not found. The Jambi Regional Fairy Tales contained in these 5 books are included in teachingmaterials because they can teach readers various moral values and provide new knowledge related to thelanguage style of fairy tales